Analisis Framing Isu Lingkungan Pada Media Online Di Papua : Framing Analysis, Environmental Issues, Sentani Flood Impact, Jayapura Regency - Indah Sulistiani; Syarifuddin; Olivian Rumangkit (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2023)
Mass media as a means of publication and campaign plays a role in raising various issues, one of which is environmental issues. The impact of environmental damage resulting in flash floods in Sentani City, Jayapura Regency, is interesting to study. The flash flood tragedy in Sentai drew the attention of many parties, both the central and local governments as well as the mass media, with the large number of victims, both loss of life and property. This study aims to analyze how the news framing carried out by the mass media in Papua in conveying environmental issues due to flash floods in Sentani City, Jayapura Regency. The research uses a qualitative research design, using framing analysis in a simple way that can be described as content analysis, social reality is interpreted and constructed with a certain meaning. The results of the study are known, the framing can be seen from the influence of the owner (manager) of the media, where for Antaranew.com is one of the state-owned media (Antara) so that the news broadcast or broadcast is attempted to be neutral and provide solutions with competent sources in the field. Meanwhile, at www.ceposoline.com, it can be seen that the two resource persons presented were quite critical, to encourage the government to pay attention to environmental issues. It's just that the news that examines the environment in the two media is very lacking or it seems that news about environmental protection is still less prestigious than the impact of environmental damage, which mostly presents about the number of victims or materials.